PENERAPAN MODEL PEMBELAJARAN DISCOVERY LEARNING UNTUK MENINGKATAN HASIL BELAJAR IPA SISWA KELAS VII MTS MUHAMADIYAH BAGAN JAWA TAHUN PELAJARAN 2015/2016 - Toni '; Yustina '; Nursal ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract: The problem of monotony still learning and using old teaching methods make the ability of mastering the concept of material and learning outcomes grade VII MTS Muhammadiyah Java Chart low. In order to encourage students to improve mastery of the concept of matter in the process of learning, the learning model used Discovery Learning. This research aims to improve the learning results of IPA students learning model with the application of Discovery Learning Class VII MTS Muhammadiyah Bagan Jawa Year 2015/2016 Lessons. This research was conducted in February and April 2016. This type of research this is a class action Research (PTK) held as much as 2 cycle. The subject of research is the grade VII MTS Java Chart Muhammadiyah that add up to 28 people. Parameters measured were the result of student learning that consists of absorption and learning of classical as well as the attitudes and skills of students in learning. Based on the results of the research the average absorbance value of Deuteronomy on the cycle I is 76.43 (good) and cycle II of deuteronomy daily increased to was 82.50 (both). Students learn classical on cycle I namely 85.71% with an average score of 87.15 and cycle II increased to 96.42% with the average value of 80.18. The attitude of students in cycle I, namely 76.68 (good) increased in cycle II becomes 92.65 (very good). The skills of students in cycle I, namely 76.04 (good) increased in cycle II becomes 83.04 (good). From the results it can be concluded that the application of Discovery Learning Learning Model can improve the results of studying biology Grade VII MTS Muhammadiyah Bagan Jawa Year 2015/2016 Lessons.Keywords: model of learning, discovery learning, the learning outcomes